Dieulafoy's disease of the bronchus: a rare cause of massive hemoptysis. Issue 2 (25th February 2014) - Smith, Ben; Hart, David; Alam, Naveed
Abstract We present the case of a 30‐year‐old non‐smoker who presented with unexplained, massive hemoptysis and was diagnosed with a rare vascular malformation.